54.5k views
4 votes
Solve the following system using the addition method:

-27x + 6y = -21
-12x +3y = -9
(3 points, 2 for work, 0.5 for each part of the solution (x,y))

User Wendel
by
5.4k points

2 Answers

7 votes

(X,Y)= (1,1)

Step-by-step explanation:

Solve the following system using the addition method: -27x + 6y = -21 -12x +3y = -9 (3 points-example-1
User Michael Vescovo
by
5.6k points
2 votes

Answer:

(x, y) = (1, 1)

Step-by-step explanation:


-27x + 6y = -21 --- (1)


-12x +3y = -9 --- (2)

Multiplying (2) by -2 to get:


24 x - 6 y = 1 8 --- (3)

Adding (1) and (3) to get:


-27x + 6y = -21


24x-6y=18

------------------------------------


-3x=-3

x = 1

Finding y:


-12(1) +3y = -9


3y=-9+12


3y=3

y = 1

Therefore, (x, y) = (1, 1).

User Augustine C
by
4.7k points